2003
DOI: 10.1089/154065803770381020
|View full text |Cite
|
Sign up to set email alerts
|

High Quality Ion Channel Analysis on a Chip with the NPC© Technology

Abstract: In evaluating ion channel function, electrophysiology, e.g., patch clamping, provides the highest information content. For the analysis of ion channel-modulating compounds, one variant of the patch-clamp technique, the whole-cell configuration, is particularly useful. We present here patch-clamp recordings in the whole-cell configuration and single channel recordings performed with planar patch-clamp chips, which are microstructured from borosilicate glass substrate. The chips are used in the Port-a-Patch, an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(26 citation statements)
references
References 16 publications
0
26
0
Order By: Relevance
“…Chien, 2003 The optimisation of planar patch-clamp cell sealing involves both biological and technological approaches. Some authors introduced new procedures in order to improve the quality of the cell suspension ( ) or optimize the identification of cells that Bruggemann et al, 2003 production of which offers high accuracy and flexibility of microstructuration and surface functionalisation. This approach has led to a model of PECVD SiO coating defining an hourglass shape of the hole ( ).…”
Section: Introductionmentioning
confidence: 99%
“…Chien, 2003 The optimisation of planar patch-clamp cell sealing involves both biological and technological approaches. Some authors introduced new procedures in order to improve the quality of the cell suspension ( ) or optimize the identification of cells that Bruggemann et al, 2003 production of which offers high accuracy and flexibility of microstructuration and surface functionalisation. This approach has led to a model of PECVD SiO coating defining an hourglass shape of the hole ( ).…”
Section: Introductionmentioning
confidence: 99%
“…Gigaseal formation and pharmacological measurements on cells using planar Si micro-apertures (Asmild et al 2003;Pantoja et al 2004), as well as glass chips (Bruggemann et al 2003;Xu et al 2003;van Stiphout et al 2005) have been successfully demonstrated. Seal resistances with hard plastic substrates did not exceed the range of a few hundred mega-ohms (Schroeder et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, CytoPatch (Cytocentrics GmbH) allows immobilization of selected cells from a flowing suspension on the CytoPatch chip by suction with a success rate of 97% and subsequent formation of gigaseals with a success rate of 68% [20]. NPC-16 utilizes a planar silicone chip that enables solution exchange on a subsecond scale [2]. A common limitation of all of these systems, however, is their limited agonist washout capabilities, which constrains the number of data points that can be obtained from a single cell.…”
Section: Discussionmentioning
confidence: 99%